2019
DOI: 10.1016/j.nicl.2019.102004
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction between dorsal caudate and salience network associated with impaired cognitive flexibility in obsessive-compulsive disorder: A resting-state fMRI study

Abstract: BackgroundImpaired cognitive flexibility has been implicated in the genetic basis of obsessive-compulsive disorder (OCD). Recent endophenotype studies of OCD showed neural inefficiency in the cognitive control network and interference by the limbic network of the cognitive control network. Exploring the relationship between the functional brain network and impaired cognitive flexibility may provide novel information about the neurobiological basis of OCD.MethodsWe obtained resting-state functional magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 80 publications
(112 reference statements)
1
20
0
Order By: Relevance
“…We employed the same inclusion and exclusion criteria as described in our previous literature (Tomiyama et al, 2019). We recruited only OCD patients who were clinically diagnosed with no another Axis I disorder.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…We employed the same inclusion and exclusion criteria as described in our previous literature (Tomiyama et al, 2019). We recruited only OCD patients who were clinically diagnosed with no another Axis I disorder.…”
Section: Subjectsmentioning
confidence: 99%
“…We employed the same clinical assessment as described in our previous literature (Tomiyama et al, 2019). All OCD patients were interviewed by using the Japanese version of the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) (Nakajima et al, 1995) to assess the severity of OCD symptoms.…”
Section: Clinical Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The preprocessing and processing of image data acquired in this study were described in our previous study (42). All participants underwent MRI scanning on a 3.0-Tesla MRI scanner (Achieva TX, Phillips Healthcare, Best, The Netherlands) equipped with standard phased array head coils.…”
Section: Image Data Acquisition and Preprocessingmentioning
confidence: 99%
“…A recent neuroimaging study, recruiting resting-state fMRI, has revealed that dysfunction of the connectivity between dorsal caudate and salience network, including the anterior insula and dorsal ACC, is related to impaired cognitive flexibility in OCD patients. However, whether this functional impairment has a causal role in the development of OCD is yet to be determined (Tomiyama et al, 2019).…”
Section: Cognitive Flexibilitymentioning
confidence: 99%